The Effects of If‐Then Plans on Weight Loss: Results of the McGill CHIP Healthy Weight Program Randomized Controlled Trial. Issue 8 (28th June 2018) - Knäuper, Bärbel; Carrière, Kimberly; Frayn, Mallory; Ivanova, Elena; Xu, Zhen; Ames‐Bull, Anaïs; Islam, Farah; Lowensteyn, Ilka; Sadikaj, Gentiana; Luszczynska, Aleksandra; Grover, Steven
Abstract : Objective: The NIH‐developed Diabetes Prevention Program (DPP) is successful in achieving clinically significant weight loss in individuals with overweight/obesity when delivered one‐on‐one. The group‐based DPP is less effective, with average weight losses of only 3.5%. The objective of this study was to increase weight loss outcomes of the group‐based DPP by integrating habit formation tools (i.e., if‐then plans). This two‐arm randomized controlled trial tested the efficacy of the habit formation–enhanced group‐based DPP compared with the standard group‐based DPP on changes in body weight (primary outcome). This study presents the 3‐ and 12‐month results of this 24‐month trial. Methods: A total of 208 participants were randomly assigned to the standard or enhanced DPP, and 172 participated. Participants were men and women with overweight/obesity who self‐reported less than 200 min/wk of exercise. Results: Both groups achieved high weight losses at 3 (5.76%) and 12 (9.98%) months, with no differences between groups (χ 2 < 1). Both groups improved in blood pressure and physical activity. Conclusions: If‐then plans did not result in higher weight loss. Both program versions resulted in higher weight loss than the group‐based DPP. This may suggest that cognitive behavioral therapy skills of the coaches (clinical psychology doctoral students) was a key factor in treatment outcome.